ASYMMETRIC WETTED SECTOR ANGLE IN WATER DISTRIBUTION OF TRAVELING GUN IRRIGATION SYSTEMS - Prado,Giuliani do (2020)
ABSTRACT This work aimed to simulate the water distribution of traveler gun irrigation, working with asymmetrical wetted angles and in windy conditions. In the simulations of a sprinkler with uniform radial profile, the following were considered: i) wetted angles between 180 and 330°; ii) wetted angle asymmetries from 0 to 90°; iii) wind speeds from 0 to 4.5 m s-1; and iv) wind direction of 0, 45, and 90°. Christiansen uniformity coefficients (CU) were calculated for strip widths from 30 to 100% of the sprinkler wetted diameter (WD). Regardless of the wetted angle adjustment, irrigations under wind speeds of 4.5 m s-1 should be avoided and strip spacings of less than 50% WD provide high CU for wind speeds up to 3.0 m s-1. For any wind conditions, asymmetries in the wetted angle led to a reduction in CU for a wetted angle of 210°. In the range of wetted angle from 270 to 330°, asymmetric adjustments of up to 20° provided a higher CU than 80% for a wind speed of 3 m s-1 and directions diagonal and perpendicular to the travel path associated with strip spacings between 60 to 70% WD, which are the spacings recommended by manufacturers of traveler irrigation machines.